HIF-1α Is a Rational Target for Future Ovarian Cancer Therapies - Wang, Xin; Du, Zhen-wu; Xu, Tian-min; Wang, Xiao-jun; Li, Wei; Gao, Jia-li; Li, Jing; Zhu, He (Frontiers in Oncology, 2021)
Ovarian cancer is the eighth most commonly diagnosed cancer among women in the world. Even though the development of novel drugs, nearly one-half of the patients with ovarian cancer die within five years of diagnosis. These situations should make us think about whether therapeutic agents for ovarian cancer deserve further exploration. Increasing evidence has shown that HIF-1α plays an important role in promoting malignant cell chemoresistance, metastasis of tumours, angiogenesis, immunosuppression and intercellular interactions. The special microenvironment, crosstalk and/or interaction between cells and other characteristics of ovarian cancer can influence the efficiency of therapy or promote the progression of the disease. Inhibition of the expression or activity of hypoxia-inducible factor-1α (HIF-1α) directly or indirectly can enhance the therapeutic responsiveness of tumour cells. Therefore, it is reasonable to consider HIF-1α as a potential therapeutic target for ovarian cancer. In this paper, we summarize the latest research on the role of HIF-1α and molecules which can inhibit HIF-1α expression directly or indirectly in ovarian cancer, and drug clinical trails about the HIF-1α inhibitors in ovarian cancer or other solid malignant tumours.